Analysis of main dynamic parameters of split power transmission - Janulevičius, Algirdas; Giedra, Kazimieras (Transport, 2008)
The review carried out had shown one basic approach of split power transmission to the organization of drive which is applied to stepless transmissions of tractors and parallel hybrid cars. In the split power transmission the power split device uses a planetary gear. Tractor engine power in the split power transmission is transmitted to the drive shaft via a mechanical and hydraulic path. The theoretical analysis of main parameters of the split power transmission of the tractor is presented. The angular velocity of sun and coronary gears of the differential set is estimated by solution of the system of equations in which one equation is made for planetary differential gear, and another ‐ for hydrostatic drive. The analysis of the transmission gear‐ratio dependencies on the ratio of hydraulic machines capacities is carried out. Dependence of the variation of angular velocity of the coronary and the sun gears on the ground speed of the tractor is presented. Dependence of sum shaft torque and its constituents, carried by mechanical and hydraulic lines, on sum shaft angular velocity and ground speed of tractor and engine speed is also presented.First published online: 27 Oct 2010